The role of coagulation/fibrinolysis during Streptococcus pyogenes infection - Loof, Torsten G.; Deicke, Christin; Medina, Eva (Frontiers in Cellular and Infection Microbiology, 2014)
The hemostatic system comprises platelet aggregation, coagulation and fibrinolysis and is a host defense mechanism that protects the integrity of the vascular system after tissue injury. During bacterial infections, the coagulation system cooperates with the inflammatory system to eliminate the invading pathogens. However, pathogenic bacteria have frequently evolved mechanisms to exploit the hemostatic system components for their own benefit. Streptococcus pyogenes, also known as Group A Streptococcus, provides a remarkable example of the extraordinary capacity of pathogens to exploit the host hemostatic system to support microbial survival and dissemination. The coagulation cascade comprises the contact system (also known as the intrinsic pathway) and the tissue factor pathway (also known as the extrinsic pathway), both leading to fibrin formation. During the early phase of S. pyogenes infection, the activation of the contact system eventually leads to bacterial entrapment within a fibrin clot, where S. pyogenes is immobilized and killed. However, entrapped S. pyogenes can circumvent the antimicrobial effect of the clot by sequestering host plasminogen on the bacterial cell surface that, after conversion into its active proteolytic form, plasmin, degrades the fibrin network and facilitates the liberation of S. pyogenes from the clot. Furthermore, the surface-localized fibrinolytic activity also cleaves a variety of extracellular matrix proteins, thereby enabling S. pyogenes to migrate across barriers and disseminate within the host. This review summarizes the knowledge gained during the last two decades on the role of coagulation/fibrinolysis in host defense against S. pyogenes as well as the strategies developed by this pathogen to evade and exploit these host mechanisms for its own benefit.